INTEGRASI FILSAFAT PENDIDIKAN DAN KEARIFAN LOKAL DALAM PENGEMBANGAN MODEL PEMBELAJARAN: KAJIAN SISTEMATIS 2020–2025 - Nurlaila, Nurlaila; Iskandar, Iskandar; Ismawati, Ismawati; Fitriati, Fitriati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT Modern education faces the challenge of globalization, which threatens to erode cultural roots and humanistic values in the learning process. This study aims to analyze trends and directions in the development of learning models based on educational philosophy and local wisdom during the 2020–2025 period. A Systematic Literature Review (SLR) with a descriptive qualitative approach was employed. Data were collected from 1,200 academic publications indexed in Crossref and Google Scholar using the Publish or Perish (PoP) application with search strings combining the terms “learning model,” “local wisdom,” and “educational philosophy.” The analysis identified three dominant research themes: (1) learning models based on local values, (2) educational philosophy and cultural context, and (3) curriculum innovation and character education. The first theme accounted for 45% of publications, followed by philosophical foundations (32%) and curriculum innovation (23%). The integration of educational philosophy and local wisdom produced the Philosophical-Local Wisdom Learning Model (PLWLM), which places cultural values at the core of the learning process. This model promotes reflective, humanistic, and character-oriented learning, aligning with UNESCO’s Education for Sustainable Development (ESD) and Indonesia’s Pancasila Student Profile. The findings highlight the urgency of developing an education system rooted in local culture while remaining adaptive to global challenges. ABSTRAK Pendidikan modern menghadapi tantangan globalisasi yang mengancam hilangnya akar budaya dan nilai humanistik dalam proses pembelajaran. Penelitian ini bertujuan untuk menganalisis kecenderungan dan arah pengembangan model pembelajaran berbasis filsafat pendidikan dan kearifan lokal pada periode 2020–2025. Kajian ini menggunakan metode Systematic Literature Review (SLR) dengan pendekatan kualitatif deskriptif. Data diperoleh dari 1.200 publikasi ilmiah yang terindeks di Crossref dan Google Scholar menggunakan aplikasi Publish or Perish (PoP) dengan kombinasi kata kunci “model pembelajaran,” “kearifan lokal,” dan “filsafat pendidikan.” Hasil analisis menunjukkan tiga tema besar dalam penelitian, yaitu (1) model pembelajaran berbasis nilai lokal, (2) filsafat pendidikan dan konteks budaya, serta (3) inovasi kurikulum karakter. Tema pertama mendominasi dengan 45% publikasi, diikuti oleh kajian filosofis (32%) dan inovasi kurikulum (23%). Integrasi antara filsafat pendidikan dan kearifan lokal menghasilkan model konseptual Philosophical-Local Wisdom Learning Model (PLWLM) yang menempatkan nilai budaya sebagai inti proses pembelajaran. Model ini mendorong pembelajaran yang reflektif, humanis, dan berorientasi karakter, sejalan dengan prinsip Education for Sustainable Development (ESD) UNESCO dan Profil Pelajar Pancasila. Temuan ini menegaskan pentingnya pengembangan pendidikan yang berakar pada budaya lokal namun adaptif terhadap tantangan global.